Biological monitoring of workers exposed to benzene in the coke oven industry. - Drummond, L (1988)
Workers in the coke oven industry are potentially exposed to low concentrations of benzene. There is a need to establish a well validated biological monitoring procedure for low level benzene exposure. The use of breath and blood benzene and urinary phenol has been explored in conjunction with personal monitoring data. At exposures of about 1 ppm benzene, urinary phenol is of no value as an indicator of uptake/exposure. Benzene in blood was measured by head space gas chromatography but the concentrations were only just above the detection limit. The determination of breath benzene collected before the next shift is non-specific in the case of smokers. The most useful monitor at low concentrations appears to be breath benzene measured at the end-of-shift.